Chemical composition and dynamics of biofilm matrix in hydrated, live Shewanella oneidensis biofilms - Ding, Yuanzhao (Nanyang Technological University, 2017)
In natural environment, microorganisms often remain attached to surfaces or interfaces as cell aggregates known as biofilms. Biofilms consist of cells embedded within a matrix of self-produced extracellular polymeric substances (EPS). The main matrix components are polysaccharides, proteins and extracellular DNA (eDNA). A wide range of physicochemical and biological attributes of biofilms, such as biofilm cohesiveness and tolerance to unfavorable conditions, are also imparted by the EPS components. Hence, to better understand biofilm structure and function, the people need to elucidate chemical composition and dynamics of the biofilm matrix. Traditional methods used to retrieve chemical information from biofilm matrix often require destructive sample preparation processes (e.g., extraction and dehydration). In particular, a vacuum environment is needed for molecular analyses involving mass spectrometry. The objective of this study was to explore the use of dynamic molecular imaging method to obtain chemical composition and dynamics of biofilm matrix in growing biofilms. Specifically, Shewanella oneidensis was used as a model organism and a novel technique combining System for Analysis at the Liquid Vacuum Interface (SALVI) with Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) was applied to elucidate chemical composition and dynamics of S. oneidensis biofilm matrix. In the first part of the thesis, one S. oneidensis mutant strain CP2-1-S1 capable of forming highly cohesive biofilms was obtained by random transposon mutagenesis. Further characterization of the mutant biofilms suggested distinct matrix composition and characteristics. Hence, S. oneidensis biofilms of the wild-type and mutant CP2-1-S1 were used for comparative studies of biofilm matrix composition and dynamics in the second part of this thesis. In the second part of this thesis, biofilm matrix chemical composition of live S. oneidensis MR-1 wild-type and the mutant CP2-1-S1 biofilms were comparatively analysed through SALVI-TOF-SIMS under hydrated conditions. The water clusters, fatty acids, matrix components (e.g., polysaccharides, proteins, lipids), bio-markers (e.g., riboflavin, signaling molecules) were directly profiled, for the first time, in live S. oneidensis biofilms. Further, chemical dynamics of biofilm matrix in the mutant CP2-1-S1 and wild-type S. oneidensis biofilms upon exposure to chromium (Cr(VI)), a model environmental perturbation, were also elucidated. The major differences between the matrix components of CP2-1-S1 and wild-type biofilms were observed with respect to fatty acids, polysaccharides, and signaling molecules. The high rate of biosynthesis of fatty acids, polysaccharides, and signaling molecules enhanced CP2-1-S1 biofilm cohesiveness and robustness. In summary, using a SALVI-TOF-SIMS technique, this thesis elucidated, for the first time, the chemical composition and dynamics of biofilm matrix for in situ live S. oneidensis biofilms under hydrated conditions. SALVI-TOF-SIMS was demonstrated to be a promising molecular imaging approach to probing chemical dynamics of in situ hydrated, live biofilms.